2017
DOI: 10.1017/s002221511700038x
|View full text |Cite
|
Sign up to set email alerts
|

Can trainees design and deliver a national audit of epistaxis management? A pilot of a secure web-based audit tool and research trainee collaboratives

Abstract: This pilot showed that trainee collaboratives can work together to deliver an audit using an encrypted data capture tool cost-effectively, whilst maintaining the highest levels of data quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The CMC model offers an appealing antidote to numerous research-based challenges in CL/P, including the bias inherent in single-center research and high running costs (Bos et al, 2007; Bhangu et al, 2014; Mehta et al, 2017; Nepogodiev et al, 2017), as well as several benefits to consultants, large research projects, clinical practice, and the clinical participants themselves (Bhangu et al, 2014; Dowswell et al, 2014; Skerritt and Hall, 2015; Mehta et al, 2017). The CMC offers opportunities for clinicians to learn and develop key research skills and to complete research projects that will result in tangible outputs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The CMC model offers an appealing antidote to numerous research-based challenges in CL/P, including the bias inherent in single-center research and high running costs (Bos et al, 2007; Bhangu et al, 2014; Mehta et al, 2017; Nepogodiev et al, 2017), as well as several benefits to consultants, large research projects, clinical practice, and the clinical participants themselves (Bhangu et al, 2014; Dowswell et al, 2014; Skerritt and Hall, 2015; Mehta et al, 2017). The CMC offers opportunities for clinicians to learn and develop key research skills and to complete research projects that will result in tangible outputs.…”
Section: Discussionmentioning
confidence: 99%
“…As a growing paradigm of health-care research, several studies have sought to evaluate the range of activity of trainee collaboratives (Bhangu et al, 2014; Dowswell et al, 2014; Skerritt and Hall, 2015; Jamjoom et al, 2016; Mehta et al, 2017; Nepogodiev et al, 2017). One large observational study of 24 surgical trainee research collaboratives in the United Kingdom (Jamjoom et al, 2016) identified more than 80 projects, 41% of which had been completed and 59% of which were currently running or under development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After piloting a data collection tool, 2 So, what of the findings? Will this revolutionise the care of epistaxis patients?…”
mentioning
confidence: 99%